Evidence-based treatment of acute otitis externa - Kim Outhoff (South African Family Practice)
Acute otitis externa (AOE), or diffuse inflammation of the external ear canal, causes a range of symptoms, including otalgia, otorrhoea, hearing loss and itching. Despite AOE being common, with a 12-month prevalence of approximately 1%, there is a paucity of evidence-based treatment guidelines. This contributes to a wide variation in its management, especially in general practice. In particular, there appears to be confusion over the roles of topical and oral antibiotics, as well as concerns about ototoxicity and the emergence of microbial resistance potentially caused by topical preparations. This article reviews the current evidence-based treatment of AOE.